The PI3K/Akt/mTOR pathway as a preventive target in melanoma brain metastasis - Tehranian, Cedric; Fankhauser, Laura; Harter, Patrick Nikolaus; Ratcliffe, Colin D H; Zeiner, Pia S.; Messmer, Julia M.; Hoffmann, Dirk C.; Frey, Katharina; Westphal, Dana; Ronellenfitsch, Michael Wilfried; Sahai, Erik; Wick, Wolfgang; et al. (Neuro-Oncology, 2022)
Brain metastases (BM) are a frequent complication of malignant melanoma (MM), with limited treatment options and poor survival. Prevention of BM could be more effective and better tolerated than treating established BM in various conditions.To investigate the temporospatial dynamics of PI3K/Akt/mTOR (PAM) pathway activation during BM formation and the preventive potential of its inhibition, in vivo molecular imaging with an Akt biosensor was performed, and long-term intravital multiphoton microscopy through a chronic cranial window in mice.In vivo molecular imaging revealed invariable PAM pathway activation during the earliest steps of brain colonization. In order to perform a long-term intravascular arrest and to extravasate, circulating MM cells needed to activate their PAM pathway during this process. However, the PAM pathway was quite heterogeneously activated in established human brain metastases, and its inhibition with the brain-penetrant PAM inhibitor GNE-317 resulted in only modest therapeutic effects in mice. In contrast, giving GNE-317 in preventive schedules that included very low doses effectively reduced the growth rate and number of BM in two MM mouse models over time, and led to an overall survival benefit. Longitudinal intravital multiphoton microscopy found that the first, rate-limiting steps of BM formation—permanent intravascular arrest, extravasation, and initial perivascular growth—are most vulnerable to dual PI3K/mTOR inhibition.These findings establish a key role of PAM pathway activation for critical steps of early metastatic brain colonization and reveal its pharmacological inhibition as a potent avenue to prevent the formation of clinically relevant BM.
Published: 03 July 2021
Gesehen am 22.03.2022